Repetition Preferences in Two-Handed Balanced Signs: Vestigial Locomotor Central Pattern Generators Shape Sign Language Phonetics and Phonology - Tkachman, Oksana; Purnomo, Gracellia; Gick, Bryan (Frontiers in Communication, 2021)
Language is produced by the body, and the body evolved to fulfill a variety of functions, most of them non-communicative. In this paper, we discuss how vestigial influences of adaptation for quadrupedal locomotion are still affecting bimanual actions, and have consequences on the manual communication systems such as sign languages of the deaf. We discuss how central pattern generators (CPGs), which are networks of nerve cells located in the spinal cord, influence bimanual actions with alternating movements to be produced with repeated motion. We demonstrate this influence with data from three unrelated sign languages, American Sign Language, British Sign Language, and Hong Kong Sign Language: in all three sign languages two-handed balanced signs produced with alternating movements have a tendency to be repeated, whereas other types of two-handed balanced signs show the opposite tendency for single movements. These tendencies cannot be fully explained by factors such as iconicity. We propose a motoric account for these results: as alternating bimanual movements are influenced by locomotor patterns, they favor repeated movements. Sign languages emerge not from scratch, but employ movement patterns that rely on old adaptations for movement.